LOGICAL AND PROBABILISTIC METHOD FOR RISK MANAGEMENT IN SOCIO-ECONOMIC SYSTEMS (ENVIRONMENT. TECHNOLOGY. RESOURCES. Proceedings of the International Scientific and Practical Conference, 2017)
In this paper we research the application of logical and probabilistic method to manage risk in socio-economic systems. Logical and probabilistic method is widely used for estimation of reliability and safety in structural complex technical systems. Authors have applied this method to estimate and analyze risk in some practical applications in economics and business. Based on risk scenario as tree of events, logics and probabilistic functions, this approach provides exact quantitative estimation of risk, risk analysis and decision-making procedures. Some promising results were obtained in banking industry and security portfolio management but application of the method has some features.